Cytomegalovirus reactivation following hematopoietic stem cell transplantation - Sanjeev Kumar Sharma; Suman Kumar; Narendra Agrawal; Lavleen Singh; Anjan Mukherjee; Tulika Seth; Pravas Mishra; Sandeep Mathur; Lalit Dar; Manoranjan Mahapatra (Journal of Infection in Developing Countries)
Introduction: There is a high prevalence of cytomegalovirus (CMV) seropositivity in developing countries. An apparent risk of CMV reactivation increases following hematopoeitic stem cell transplantation. With effective surveillance and timely treatment using anti-viral therapy, morbidity and mortality associated with CMV reactivation can be reduced. Objectives: To evaluate the incidence and morbidity associated with CMV reactivation following hematopoeitic stem cell transplantation. Methodology: We retrospectively analysed 136 hematopoeitic stem cell transplant recipients at our centre for CMV reactivation and their complications. Quantification of CMV-DNA was done by PCR. CMV disease was confirmed histologically via CMV inclusion bodies or immunostaining of biopsy of the affected organ, mainly the gastrointestinal tract. Results: A total of 13 out of 136 patients (9.56%) had CMV reactivation. 6 out of 13 patients had CMV disease, 3 of which died (23.1% of patients with CMV reactivation). CMV reactivation occurred at a median duration of 52.5 days post transplantation (range 35-178 days). The gastrointestinal tract was the organ most commonly affected by CMV. The median follow-up was 14 months (range 6 - 64 months). Conclusion: Through a higher rate of sero-prevalance in developing countries, the incidence of CMV infection following hematopoeitic stem cell transplantation is comparable to that reported in Western literature. Oral valganciclovir was an effective pre-emptive therapy for CMV disease.